NEWS FROM THE ANNUAL CONGRESS OF EUROPEAN SOCIETY OF CARDIOLOGY (BARCELONA 2014): REALIZED AND UNREALIZED EXPECTATIONS - S. Y. Martsevich; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии)
News from Congress of the European Society of Cardiology (Barcelona, 2014) is highlighted. Results of recent controlled clinical trials, new clinical recommendations and registers data that were presented at the Congress are discussed.